Social Support as a Moderator of Self Efficacy and Learning Motivation Towards Students' Academic Hardiness - Risyda Azizah Mukhtar; Fadhilah Suralaga; Devie Yundianto (‎‎‎TAZKIYA Journal of Psychology, 2023)
This research examined the factors that influence academic hardiness in tahfiz lessons. The author suspects that the factors contained in the social support variable are moderator variables for the variables self-efficacy, learning motivation, and gender which influence academic hardiness. This research uses a quantitative approach with multiple regression analysis. The sample consisted of 150 students in class 5 and class 6 of Islamic school X who were taken using a purposive sampling technique. In this research, the measuring tool used is the revised academic hardiness scale (RAHS) to measure the academic hardiness variable. Multi-Dimensional Scale of social support (Zimmet et al., 1988) to measure social support variables. The self-efficacy scale will be measured based on Bandura's theory to measure the dimensions of magnitude, generality, and strength. Learning motivation is measured using intrinsic and extrinsic aspects (Woolfolk, 1995). The research results show three significant regression coefficients: self-efficacy, intrinsic learning motivation, and gender. All three are influenced by social support, increasing students' academic hardiness. The author hopes that the implications of the results of this research can be reviewed and developed in further research. For example, adding other variables related to academic hardiness, such as parental and learning styles.